KEANEKARAGAMAN TUMBUHAN SEKITAR AREAL PENANAMAN W-BRIDGE PROJECT DI TAHURA SULTAN ADAM KALIMANTAN SELATAN - Trisnu Satriadi; Mahrus Aryadi (EnviroScienteae, 2014)
The aim of this research was to know the biodiversity of flora around the W - bridge reforestation project area in Forest Parks of Sultan Adam, South Kalimantan.  The research method used field survey with a purposive sampling and using the line transect.  Based on analysis found that at the bottom block, found 8 ground vegetations, 11 seedlings, 14 saplings, 7 poles and 10 trees. Dominant vegetation for ground vegetation is Laladingan (Pogonatherum sp.), for seedling is Tengkook Ayam (Cryptocarya sp.), for sapling and pole are Mahang (Macaranga sp.), and for tree is Jambu Burung (Eugenia sp.). At the top block, found 15 ground vegetations, 17 seedlings, 12 saplings , 6 poles, and 5 trees. Dominant vegetation for ground vegetation is Tempukas, for seedling is Tengkook Ayam, for sapling and pole are Alaban Kapas (Vitex pubescens) and for tree is Bangkinang Burung (Ficus sp.). Both of blocks has moderate diversity index (1.540 - 2.564) and low similarity index (0 - 20.588).